MRGPRX2 signaling involves the Lysyl-tRNA synthetase and MITF pathway - Guo, Yanru; Ollé, Laia; Proaño-Pérez, Elizabeth; Aparicio, Cristina; Guerrero, Mario; Muñoz-Cano, Rosa; Martín, Margarita (Frontiers in Immunology, 2023)
MRGPRX2, a G-coupled-seven transmembrane domain receptor, is mainly expressed in mast cells and neurons and is involved in skin immunity and pain. It is involved in the pathophysiology of non-IgE-mediated immediate hypersensitivity and has been related to adverse drug reactions. Moreover, a role has been proposed in asthma, atopic dermatitis, contact dermatitis, and chronic spontaneous urticaria. Although its prominent role in disease, its signaling transduction is poorly understood. This study shows that MRGPRX2 activation with substance P increases Lysyl t-RNA synthetase (LysRS) translocation to the nucleus. LysRS is a moonlighting protein with a dual role in protein translation and IgE signaling in mast cells. Upon allergen- IgE-FcRI crosslinking, LysRS is translocated to the nucleus and activates microphthalmia-associated transcription factor (MITF) activity. In this study, we found that MRGPRX2 triggering leads to MITF phosphorylation and increased MITF activity. Therefore, overexpression of LysRS increases MITF activity after MRGPRX2 activation. MITF silencing revealed a reduction in MRGPRX2 signaling, decreasing calcium influx and reducing mast cell degranulation. Furthermore, a MITF pathway inhibitor, ML329, reduces MITF expression, calcium influx, and mast cell degranulation. Moreover, drugs such as atracurium, vancomycin, and morphine, reported to induce MRGPRX2-dependent degranulation, increase MITF activity. Altogether, our data show that MRGPRX2 signaling increases MITF activity, and abrogation of that by silencing or inhibition results in defective MRGPRX2 degranulation. We conclude that MRGPRX2 signaling involves LysRS and MITF pathways. Thus, MITF and MITF-dependent targets may be considered therapeutical approaches to treat pathologies where MRGPRX2 is implicated.